The Child in Trouble: The Long and Difficult Road to Reforming the Crazy-Quilt Juvenile Justice System - Irving R. Kaufman (Washington University Law Quarterly, 1982)
In this Article, I will outline a comprehensive approach toward reforming the juvenile justice system to enable it to better serve the needs of society and the child. Reform must be based on the fundamental premise that the prescription of treatment or services by juvenile authorities is not inherently beneficial to the juvenile and should be utilized with restraint. Institutionalization, much closer to punishment than to treatment, must not masquerade as rehabilitation. Accordingly, I will detail a variety of fundamental changes in the framework of the juvenile justice system which could take us a long way down the road to needed reforms. It will become clear that the central shortcoming in our efforts to help the child in trouble is the absence of a comprehensive system with centralized authority over all aspects of the child's interaction with the law. In this connection, I will suggest proposals for unifying the system's remedial efforts and eliminating gaps and duplication in services. The linchpin of this comprehensive reform would be the creation of a coordinating organization, requiring, as a first step in each case, the assignment of juvenile cases to trained impartial overseers whose focus will be the rehabilitation of the family.
Keywords: Juvenile courts